2016
DOI: 10.5713/ajas.15.0865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a specific blend of essential oils on apparent nutrient digestion, rumen fermentation and rumen microbial populations in sheep fed a 50:50 alfalfa hay:concentrate diet

Abstract: ObjectiveAn experiment was conducted to investigate the effects of a specific mixture of essential oils (MEO), containing thyme, clove and cinnamon EO, on rumen microbial fermentation, nutrient apparent digestibility and blood metabolites in fistulated sheep.MethodsSix sheep fitted with ruminal fistulas were used in a repeated measurement design with two 24-d periods to investigate the effect of adding MEO at 0 (control), 0.8, and 1.6 mL/d on apparent nutrient digestibility, rumen fermentation characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
4
12
3
1
Order By: Relevance
“…However, plasma levels of total protein (TP), albumin, globulin, urea, triglycerides (TG), high density lipoprotein (HDL), total antioxidant capacity, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were not influenced by addition of EO. The lack of influence of EO on some blood parameters consistent with Vakili et al (2013) who used thyme oil in diets of feedlot calves, Unal and Kocabagli (2014) with thyme in lamb ration and they found no effect on TC, TG, HDL and LDL and in another study, Khateri et. al.…”
Section: Blood Metabolitessupporting
confidence: 62%
See 1 more Smart Citation
“…However, plasma levels of total protein (TP), albumin, globulin, urea, triglycerides (TG), high density lipoprotein (HDL), total antioxidant capacity, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were not influenced by addition of EO. The lack of influence of EO on some blood parameters consistent with Vakili et al (2013) who used thyme oil in diets of feedlot calves, Unal and Kocabagli (2014) with thyme in lamb ration and they found no effect on TC, TG, HDL and LDL and in another study, Khateri et. al.…”
Section: Blood Metabolitessupporting
confidence: 62%
“…The evaluation of EO for antimicrobial, antifungal and antioxidant properties has been conducted by humans in traditional medicine and there were much research on the use of plant extracts and EO in animal production all over the world (Khateri et. al., 2017).…”
mentioning
confidence: 99%
“…Although DCP% and nitrogen retention was improved with EO supply (table 4 and 5) that resulted in increased milk's protein with these EO (table 9). However, Khateri et al (2017) recorded that total protein and albumin were not influenced by the added mixture of EO. Serum urea and creatinine were unaffected by any of EO.…”
Section: Blood Serum Parametersmentioning
confidence: 95%
“…It should be noted that in the present study the effective concentration of EO was calculated based on their principal compound; for example, THY and THY-C have the same concentration of THY-C. Despite some blends of EO (Khateri et al, 2017) and EOC (Newbold et al, 2004) have been tested in vivo and in vitro (Castillejos et al, 2005) with generally depressing or no effect on fermentations, we are not aware of any study examining the interactions between compounds; however our results suggest that interactions of compounds of EO may occur indicating or not an additive effect. In this direction are the results of Rofiq and Gorgulu (2014), who found an antagonistic effects between CLO and orange peel oil at 300 ppm when they were used together in combination treatment for in vitro digestion of dairy TMR.…”
Section: Discussionmentioning
confidence: 94%
“…This result was not supported by our data showing a reducing effect of CIN-C on TMR NDFD24 and a lack of effect of CIN, CLO and EUG. A lack of effects was found by Khateri et al (2017), that demonstrated no effect of a blend including CLO and CIN (together with THY) on in vivo sheeps (fed a 50:50 forage to concentrate ratio diet) apparent total tract digestibility of DM, CP, organic matter, and NDF. Moreover, CLO appeared to reduce NDFD24 of soyabean meal and maize grain, while EUG decreased only the NDFD4 of soyabean meal.…”
Section: Discussionmentioning
confidence: 96%